Kemampuan Pemecahan Masalah Mahasiswa dalam Menyelesaikan Masalah Matematika pada Mata Kuliah Aljabar Linier - Novitasari, Pratiwi; Aisyah, Amiratih Siti (CV. Kurnia Grup, 2024)
This type of research is descriptive qualitative research which aims to describe students' problem solving abilities in solving problems related to linear algebra. The subjects in this research were 4th semester mathematics education students. The instruments in this research include linear algebra questions and an interview guide. The research subjects included two students in the high and low categories. Subjects in the high category are able to fulfill all indicators of problem-solving ability which include, being able to understand problems, being able to plan problem-solving strategies, being able to implement strategies, and subjects re-examining the results of their work. Subjects in the low category are less able to fulfill the first indicator of problem-solving ability, namely understanding the problem, and are unable to fulfill the indicators of planning a strategy, implementing a strategy, and not checking the results of their work again.